Policy diffusion and transfer of the Bologna Process in Africa's national, sub-regional and regional contexts - Eta Elizabeth Agbor; Mngo Zachary Y (SAGE PUBLICATIONS LTD, 2022)
This article traces the process of diffusion and transfer of the European Bologna Process reforms in Africa's national, sub-regional and regional contexts and examines factors that drive these processes. Considering that African countries are not official signatories but are aligning their systems of education to the BP, and in the absence of a coordinated effort and the use of digital technology to produce and present data that documents and maps out progress, tracing the diffusion process in this context is challenging, which is the reason for limited research in this area. Based on a review of existing literature, this article argues that in Africa, the dissemination and transfer of BP-related reforms started as individual projects by national governments as early as 2000 before metamorphosing into sub-regional and regional initiatives. The article identifies economic, political and discursive factors as well as the selective and silent processes that shaped Bologna transfer at these different levels in Africa.